Analisis Faktor Lingkungan Yang Mempengaruhi Tingkat Kecemasan Pelayanan Kesehatan Anak Di Puskesmas Pubalingga - Taat Sumedi (JURNAL KEPERAWATAN MERSI, 2020)
Background: Sick children should be taken to the health services of the Primary Level Service Unit at the Puskesmas (UPTD) first, with their families is a stressful experience, both for children and parents. Some scientific evidence shows that the health center environment itself is a major cause of stress for children and parents, both physical environments such as buildings or nursing rooms, equipment, distinctive odors, white clothes for health workers and the social environment, such as fellow child patients, or interactions and health workers themselves Scientific research illustrates that the health center environment causes major stress for both children and their parents, including the physical environment, and the social environment such as interactions between patients between children, and even the attitudes reflected by doctors and nurses.Metode: To see the factors that affect the error rate in children who seek treatment at Purbalingga Health Center.This research is a research that carries out a cross-sectional design, purposive sampling method, and chi square statistical analysis.Result: Based on the results of the study, 7 patients (30,458%) who underwent short and medium-term treatment experienced normal loss. Most of the respondents in the age range of 4-8 years and 9-11 years were in the medium anxiety category as many as 18 respondents (69.55%). Children aged 4-8 years who have just entered school and lack of interaction with the surrounding environment will experience anxiety more often, in fact there are 4 respondents (8.70%) of whom experience severe anxiety compared to those above.It shows that the proportion of anxiety in the sexes of men and women is almost the same. Two male respondents (4.80%) were in the mild anxiety category, 7 respondents (31.68%) were in the moderate category and 3 respondents (4.35%) were in the heavy category. Likewise, 3 respondents (8.70%) were in the mild anxiety category, 10 respondents (40.12%) were in the moderate category, and 5 respondents (10.35%) were in the severe anxiety category. Shows environmental factors, 13 respondents (52.17%) who enter into moderate anxiety and feel familiar with the environment and 8 respondents (26.09%) feel unfamiliar with the environmental conditions of all 18 respondents (65.22%), feel the environment that is felt familiar.Conclusion: length of treatment, the activities constraint, and separated, it means that there is influence toward apprehensive level in children getting puskesmas